Implementasi Prompt-Based Learning Berbasis AI Video Generator untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Syarah Nur Sabrina; Andi Kristanto (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
The use of artificial intelligence in the field of education offers opportunities to create more creative and student-centered learning. In elementary schools, many students face difficulties when required to construct persuasive sentences logically and critically. This study aims to explain how prompt-based learning, assisted by an AI video generator, is applied to enhance students' critical thinking skills in learning persuasive sentences. This research employs a descriptive qualitative approach and involves elementary school students. Data were collected through classroom observations, student work results, and reflective notes. Students were asked to create prompts containing persuasive messages, communication objectives, and the target audience or readers. These prompts were then transformed into short videos using the Flow AI tool. Data were analyzed thematically to examine the development of critical thinking and the level of student engagement. The results show that prompt-based learning assisted by AI technology increases students' motivation, participation, and engagement in learning. Students demonstrated improved abilities in analyzing persuasive messages, organizing ideas logically, understanding communication objectives, and critically considering the target audience. Additionally, the use of AI-generated videos made the learning process more interactive and meaningful. This study concludes that integrating AI-based technology with appropriate learning approaches can effectively support the development of critical thinking and student-centered learning at the elementary education level.